A Nationwide Survey of Hepatitis E Virus Infection and Chronic Hepatitis in Heart and Kidney Transplant Recipients in Japan - Owada, Yohei (Transplantation, 2020)
BACKGROUND. Recently, chronic hepatitis E has been reported in solid organ transplant (SOT) recipients in European countries. Previously, we clarified the prevalence of hepatitis E virus (HEV) infection in Japanese liver transplant recipients and identified 2 chronic hepatitis E patients infected by blood transfusion. However, the rate of HEV infection in recipients of SOTs other than liver in Japan remains unclear, so we conducted a nationwide survey to clarify the prevalence of chronic HEV infection in Japanese heart and kidney transplant recipients. METHODS. A total of 99 heart and 2526 kidney transplant recipients in 17 hospitals in Japan were examined for the presence of the IgG class of anti-HEV antibodies as well as for serum HEV RNA. RESULTS. The prevalence of anti-HEV IgG among heart and kidney transplant recipients was 7.07% (7/99) and 4.08% (103/2526), respectively. One heart transplant patient (1.01%) and 11 kidney transplant patients (0.44%) were found to be positive for HEV RNA. The HEV isolates from all viremic patients were typed as genotype 3. Four patients developed chronic hepatitis E after transplantation. Three patients were treated with ribavirin; their liver enzymes normalized, and HEV RNA became negative immediately. Sustained virologic response was achieved in all cases. CONCLUSIONS. This is the first nationwide survey of HEV infection in Japanese heart and kidney transplant recipients. The prevalence of anti-HEV IgG and HEV RNA in heart and kidney transplant recipients in Japan was lower than that in European countries. Of note, 42% of viremic transplant patients developed chronic hepatitis.